Understanding literature reviews: Implications for music therapy. Issue 2 (15th March 2018) - Matney, Bill
ABSTRACT: Social science and health care researchers, including music therapy researchers, have conducted various types of literature reviews; these types have largely been understood as either traditional or systematic reviews. However, authors, both within and outside of music therapy, have used mixed terminology, provided questionable rationales for categorization, disagreed about categorization, or used ambiguous language to describe broad review methodologies. As an alternative to categorization, one could view literature review processes and methodologies from the standpoint of historical development and methodological value; each methodology answers different types of questions through review's characteristics. The purpose of this article is to present a comprehensive overview of literature review processes and methodologies by (a) describing the general purposes of narrow and broad literature reviews, (b) providing a historical overview of broad reviews, and (c) describing broad review methodologies in relation to their respective definitions, histories, methodological characteristics, purposes, example questions, and study examples from healthcare and music therapy literature. After providing a general overview of categories and histories of reviews, the author analyzes a total of 25 broad literature review methodologies and 2 salient broad review procedures. The author then discusses implications for music therapy research and practice, specifically in relation to current broad review publications, policy development, information flow, stakeholder engagement, and tertiary reviews. Furthermore, this article may act as an initial reference for researchers and educators.